Management Strategies for Pediatric Moderate-to-Severe Plaque Psoriasis: Spotlight on Biologics - Ruggiero A; Portarapillo A; Megna M; Patruno C; Napolitano M (Dove Medical Press, 2023)
Angelo Ruggiero,1 Antonio Portarapillo,1 Matteo Megna,1 Cataldo Patruno,2 Maddalena Napolitano1 1Section of Dermatology, Department of Clinical Medicine and Surgery, University of Naples Federico II, Naples, 80131, Italy; 2Department of Health Sciences, University Magna Graecia of Catanzaro, Catanzaro, ItalyCorrespondence: Maddalena Napolitano, Section of Dermatology, Department of Clinical Medicine and Surgery, University of Naples Federico II, Via Pansini 5, Naples, 80131, Italy, Tel +393396215845, Email maddy.napolitano@gmail.comAbstract: Although psoriasis onset has been reported at any ages, in up to one-third of cases, it begins during childhood, with an estimated prevalence of about 2% in pediatric population. The management of moderate-to-severe forms of childhood psoriasis may represent a challenge for dermatologists, especially for parents' concerns about the need of systemic treatments. However, a prompt safe and effective treatment is mandatory in these patients, due to the significative impact that psoriasis may have on their quality of life, with well-known consequences on psychological health of both patients and caregivers. Due to the relatively frequent parents' refusal of systemic treatments, probably due to the fear of eventual adverse events, difficulties of oral or injective route, the management of moderate-to-severe forms still represents a challenge. Herein, we report a narrative review, aiming to resume the systemic treatments for pediatric psoriasis, focusing on the use of biologics and small molecules in the pediatric ages. The most widely used therapeutic strategies today for the pediatric population with moderate-severe psoriasis are traditional systemic therapies, while more innovative drugs such as biologics and small molecules now represent a somewhat unexplored but certainly promising field for unresponsive patients.Keywords: psoriasis, biologics, childhood, pediatric, small molecules, treatment